The Selective Oral Immunomodulator Vidofludimus in Patients with Active Rheumatoid Arthritis: Safety Results from the COMPONENT Study - Andreas Muehler; Hella Kohlhof; Manfred Groeppel; Daniel Vitt (Adis, Springer Healthcare, 2019)
Abstract Introduction The dihydroorotate dehydrogenase (DHODH) inhibitors leflunomide and teriflunomide are immunomodulatory agents approved to treat rheumatoid arthritis (RA) and multiple sclerosis, respectively, and are actively being investigated as therapeutic agents for other immune-related diseases; however, both structurally related compounds have a number of potentially serious adverse effects. Vidofludimus, a new selective second-generation DHODH inhibitor, is chemically distinct from leflunomide/teriflunomide and appears to exhibit a distinct safety profile. Objective The aim of the COMPONENT study was to assess the efficacy, safety, and pharmacokinetics of vidofludimus in the treatment of patients with active RA on a background therapy of methotrexate. This report focuses solely on the safety results of the COMPONENT trial. Methods Patients received once-daily oral vidofludimus (N = 122) or placebo (N = 119) along with their standard of care methotrexate treatment for 13 weeks. Efficacy endpoints were assessed. Safety parameters were monitored throughout treatment and at follow-up. Plasma concentrations of vidofludimus were measured. Results The primary efficacy endpoint, American College of Rheumatology 20 (ACR20) responder rate at 13 weeks, demonstrated numerical superiority in the treatment group compared with placebo; however, it did not reach statistical significance. Nonetheless, the COMPONENT study yielded important safety and pharmacokinetic data that could provide important information regarding the use of vidofludimus in other clinical trials, not only for RA but also for other autoimmune diseases. A safety profile for vidofludimus similar to placebo was obtained in this RA patient population. This includes similar rates of the adverse events of diarrhea, alopecia, neutropenia, and elevated liver enzymes, all of which are known drug-related adverse events reported for leflunomide and teriflunomide. A potential pharmacokinetic interaction between vidofludimus and methotrexate was observed. Conclusions Vidofludimus demonstrated a positive safety profile, making it a promising candidate for the treatment of a variety of immune-related diseases. Trial Registrations ClinicalTrials.gov identifier: NCT01010581.